Influence of state structural policy upon the development of economy: theoretical approach based on Ukrainian experience (Research Bulletins of the Faculty of Economic Sciences, 2015)
State regulation of structural changes in an economy is aimed at forming and support of a rational economic structure and is carried out through state structural policy. The goal of the article is to define the directions for substantiation of state structural policy, which could ensure the development of the national economy; determine its priorities and a mechanism of its implementation. The essence of the structure of state economy is given, main directions for implementation of state structural policy are offered, including the industrial, innovational and investment policies, development of which influences the economic growth and the increase of national competitiveness on a global level.
Keywords: investments; innovations; competitiveness; industry; structural changes; state structural policy